Stabilized Perovskite Quantum Dot Solids via Nonpolar Solvent Dispersible Covalent Ligands - Sanghun Han; Gayoung Seo; Taeyeong Yong; Seongmin Choi; Younghoon Kim; Jongmin Choi (Advanced Science, 2023)
Abstract The ligand exchange procedure of CsPbI3 perovskite quantum dots (PQDs) enables the fabrication of thick and conductive PQD solids that act as a photovoltaic absorber for solution‐processed thin‐film solar cells. However, the ligand‐exchanged CsPbI3 PQD solids suffer from deterioration in photovoltaic performance and ambient stability due to the surface traps, such as uncoordinated Pb2+ sites on the PQD surface, which are generated after the conventional ligand exchange process using ionic short‐chain ligands dissolved in polar solvents. Herein, a facile surface stabilization is demonstrated that can simultaneously improve the photovoltaic performance and ambient stability of CsPbI3 PQD photovoltaic absorber using covalent short‐chain triphenylphosphine oxide (TPPO) ligands dissolved in a nonpolar solvent. It is found that the TPPO ligand can be covalently bound to uncoordinated Pb2+ sites and the nonpolar solvent octane can completely preserve the PQD surface components. Owing to their synergetic effects, the CsPbI3 PQD photovoltaic absorber stabilized using the TPPO ligand solution dissolved in octane exhibit higher optoelectrical properties and ambient stability than the control absorber. Consequently, CsPbI3 PQD solar cells composed of PQD photovoltaic absorbers fabricated via surface stabilization strategy provide an improved power conversion efficiency of 15.4% and an enhanced device stability.